PENINGKATAN KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI PENDAMPINGAN BERBASIS BIMBINGAN INDIVIDU DI SDN 03 BATANG GASAN - Yefreni, Bailis (Jurnal Manajemen Pendidikan, 2018)
Based on the results of observations and supervision carried out by the author, it shows that teachers in SDN 03 Batang Gasan do not have the ability and skills that are good at carrying out their duties, especially in terms of using learning media. The purpose of this study was to describe and obtain information about efforts to improve the ability of teachers to use learning media by conducting individual guidance-based mentoring at SDN 03 Batang Gasan. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 3 class teachers at SDN 03 Batang Gasan. The research data was collected using observation sheets. Data were analyzed using averages. The results of the study show that mentoring activities based on individual guidance can improve the ability of teachers to design, determine and use learning media. This is evidenced based on preliminary data on the ability of teachers before the implementation of individual guidance-based mentoring activities is still in the poor category. Then after the individual guidance-based mentoring activities, the teacher's ability increased which was seen from the improvement of the quality of the learning media made by the teacher and the increase in the teacher's ability to use the media in the class to 79.67 (good) in the first cycle to 87.33 (very good).